AUTEN-67, an autophagy-enhancing drug candidate with potent antiaging and neuroprotective effects. Issue 2 (1st February 2016) - Papp, Diána; Kovács, Tibor; Billes, Viktor; Varga, Máté; Tarnóci, Anna; Hackler, László; Puskás, László G; Liliom, Hanna; Tárnok, Krisztián; Schlett, Katalin; Borsy, Adrienn; Pádár, Zsolt; et al.
Abstract: Autophagy is a major molecular mechanism that eliminates cellular damage in eukaryotic organisms. Basal levels of autophagy are required for maintaining cellular homeostasis and functioning. Defects in the autophagic process are implicated in the development of various age-dependent pathologies including cancer and neurodegenerative diseases, as well as in accelerated aging. Genetic activation of autophagy has been shown to retard the accumulation of damaged cytoplasmic constituents, delay the incidence of age-dependent diseases, and extend life span in genetic models. This implies that autophagy serves as a therapeutic target in treating such pathologies. Although several autophagy-inducing chemical agents have been identified, the majority of them operate upstream of the core autophagic process, thereby exerting undesired side effects. Here, we screened a small-molecule library for specific inhibitors of MTMR14, a myotubularin-related phosphatase antagonizing the formation of autophagic membrane structures, and isolated AUTEN-67 (autophagy enhancer-67) that significantly increases autophagic flux in cell lines and in vivo models. AUTEN-67 promotes longevity and protects neurons from undergoing stress-induced cell death. It also restores nesting behavior in a murine model of Alzheimer disease, without apparent side effects. Thus, AUTEN-67 is a potent drug candidate for treating autophagy-related diseases.